Generation of Weak Coherent Pulses for Quantum Cryptography Systems - Yassien, Fuad A.; Tawfeeq, Shelan K.; Khalil, Ahmed I.; Aziz, Farah R. (Iraqi Journal of Laser, 2010)
This work is a trial to ensure the absolute security in any quantum cryptography (QC) protocol via building an effective hardware for satisfying the single-photon must requirement by controlling the value of mean photon number. This was approximately achieved by building a driving circuit that provide very short pulses (≈ 10 ns) for laser diode -LD- with output power of (0.7-0.99mW) using the available electronic components in local markets. These short pulses enable getting faint laser pulses that were further attenuated to reach mean photon number equal to 0.08 or less.